Niewykorzystana szansa. O niedoszłym do skutku dialogu aksjologicznym Ingardena i Elzenberga - Andrzej Lorczyk (Studia Philosophica Wratislaviensia)
In this paper, I take as a starting point an exchange between Henryk Elzenberg and Roman Ingarden concerning the mode of existence of values. Based on their correspondence, I attempt to trace the missed and lost opportunities for dialogue between the two great Polish axiologists. I demonstrate that while sharing an intense interest in the issue of the existence of values, they addressed them independently and in divergent ways. Following that, I also look at the posthu- mous fate of their unfinished dialogue and argue that their work opens a space for further exploration of the ontology of values.